Podcast Experiences: EFL Students' Challenges and Strategies in Listening to English - Selviani , Tri; Ardiana, Ardiana (Universitas PGRI Adi Buana Surabaya, 2025)
Listening is a fundamental skill in language acquisition; however, many EFL learners still face real challenges in understanding spoken English. Podcasts offer an innovative and accessible medium for self-directed learning, making them a potential solution for improving listening skills. This study examines the challenges and strategies students use to improve their English listening skills through podcasts. A qualitative descriptive design was used, involving 10 English Education students who engaged with podcasts as part of their learning. Data were collected through semi-structured interviews, conducted both on campus and via phone, and analyzed qualitatively by transcribing and organizing the data to identify students' challenges and strategies. The findings reveal that students face various obstacles such as speech speed, diverse accents, unfamiliar vocabulary, and idiomatic expressions, which can hinder comprehension. To overcome these challenges, students adopt strategies such as using subtitles, adjusting playback speed, re-listening to difficult segments, and taking detailed notes on new words and phrases. These approaches helped students increase their vocabulary, strengthen listening comprehension, and engage more deeply with the content. The findings highlight the effectiveness of combining tailored strategies with podcasts, emphasizing their potential as a valuable tool for language development. This study offers useful insights for educators and learners alike, underscoring the importance of flexible learning methods to address various difficulties in English listening comprehension.